Knowledge dissemination and selection of climate resilient rice varieties and their demand aggregation in Odisha through a digital tool —SeedCast - CGIAR Research Program on Climate Change, Agriculture and Food Security (2019)
SeedCast tool has been successfully piloted in the Kharif (rainy) season of 2019. Out of the total of 30 districts in Odisha, 23 were covered and dealers from these districts have been oriented on the functionality of the tool.